(untitled) (Journal of Nepalese Business Studies, 2021)
The primary objective of this paper is to describe and measure financial status of the Bishowkarma, Pariyar, and Nepali caste in the rural and urban regions of Kaski district of Nepal. The study has used descriptive research design and judgmental and quota sampling with an equal 150 samples of the rural and urban areas including 50 samples of each caste. A set of close-ended questionnaires was used to collect data from primary sources. The collected data were analyzed with the help of statistical tools like frequencies, weighted mean, and percentage using MS-Word, MS-Excel, and SPSS. The Bishwokarma caste has good financial status in the urban area followed by Nepali and Pariyar. However, in a rural area, the Nepali caste has a better financial position followed by Pariyar and Bishwokarma. The study results indicate people living in the urban areas have a stronger financial position with an overall mean score of 3.02 compared to people living in the rural areas with an overall mean score of 2.85. The concerned government bodies need to give special care to uplift the financial status of the Pariyar people in the urban region and the Bishwokarma people in the rural region. Thus, this study conveys a comprehensive picture of the financial status of rural and urban Dalits of Kaski District which could be the baseline data set for future study and primary data sources for local stakeholders.